Beyond the Classroom: Investigating EFL Students’ Self-Endeavors in Enhancing English Language Learning Within the Emerging AI Era - Irpan Apandi Batubara; Khairul Azmi (ITScience (Information Technology and Science), 2026)
The emergence of artificial intelligence (AI) technologies has transformed English language learning practices in higher education by encouraging more autonomous, flexible, and digitally mediated learning behaviors among students. This study investigates students’ self-efficacy in English language learning in the emerging AI era at an Islamic university in Riau, Indonesia. Using a qualitative case study design, this study conducted a semi-structured interview with 30 university students. The collected data were analyzed using thematic analysis. The results show that students used a variety of self-endeavors to enhance their English language learning, which fall into several main categories: informal English exposure through digital media; self-regulated vocabulary and language development; social interaction and communication practice; autonomous writing and reflective learning; and technology-assisted and AI-oriented learning practices. The study concludes that EFL students in the emerging AI era enhanced their English language learning beyond the classroom through self-directed, technology-mediated, and socially situated learning practices.